2016
DOI: 10.1161/hypertensionaha.115.06752
|View full text |Cite
|
Sign up to set email alerts
|

Prehypertension in Pregnancy and Risks of Small for Gestational Age Infant and Stillbirth

Abstract: Abstract-It is not fully known whether maternal prehypertension is associated with increased risk of adverse fetal outcomes, and it is debated whether increases in blood pressure during pregnancy influence adverse fetal outcomes. We performed a population-based cohort study in nonhypertensive women with term (≥37 weeks) singleton births (n=157 446). Using normotensive (diastolic blood pressure [DBP] <80 mm Hg) women as reference, we calculated adjusted odds ratios with 95% confidence intervals between prehyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 48 publications
0
26
1
1
Order By: Relevance
“…The decline in SV throughout gestation could not be compensated by the rise in HR, resulting in mild drop in CO. PVR remained static across gestation in screen-positive women, a failure of the cornerstone of hemodynamic maternal adaptation in early pregnancy. Previous studies on maternal hemodynamics, performed in either hypertensive populations [27][28][29] or in normotensive cohorts [10][11][12][30][31][32][33][34][35][36] , had similar findings of low CO and raised PVR in pregnancies with FGR.…”
Section: Discussionmentioning
confidence: 68%
“…The decline in SV throughout gestation could not be compensated by the rise in HR, resulting in mild drop in CO. PVR remained static across gestation in screen-positive women, a failure of the cornerstone of hemodynamic maternal adaptation in early pregnancy. Previous studies on maternal hemodynamics, performed in either hypertensive populations [27][28][29] or in normotensive cohorts [10][11][12][30][31][32][33][34][35][36] , had similar findings of low CO and raised PVR in pregnancies with FGR.…”
Section: Discussionmentioning
confidence: 68%
“…The influence of pre‐HT on birth outcomes in SSA is not clear but recent reports from higher income countries have reported that pre‐HT early in pregnancy was associated with an increased risk of small for gestation age, pregnancy induced hypertension, neonatal sepsis and perinatal mortality . Therefore, without appropriate intervention, over one third of women in our study could potentially be at risk of adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 82%
“…This is of particular interest because blood pressure is directly related to adverse pregnancy outcomes and may increase the chance of lowfor-gestational-age births. 29,30 Although in monsoon season women can often rely on rainwater, they will have to switch to a higher saline source if their pregnancy also covers (part of) the dry season. The increases in blood pressure that can be caused by this change in source could significantly increase the risk of adverse pregnancy outcomes especially because such increase would push the blood pressure of the women into the (pre)hypertensive range.…”
Section: Discussionmentioning
confidence: 99%